REACTION OF ISLAMIC STOCK MARKET TO MACROECONOMIC VARIABLES: A STUDY OF INDIA AND INDONESIA - Irfan, Mohammad; Kassim, Salina; Dhimmar, Sonali; Zahid, Mohd; Fuadi, Nasrul Fahmi Zaki (Universitas Airlangga, 2021)
India and Indonesia are among the world-largest democracies, having a strong international presence through involvement in various economic and intergovernmental organizations such as in the E7 countries and G20 countries groups. This study aims to identify the impact of macroeconomic variables on the Islamic stock markets of India and Indonesia. Two Islamic stock market indices are considered: the Indian Bombay Stock Exchange (BSE) Shariah Index and the Indonesian Jakarta Islamic Index (JII). At the same time, the macroeconomic variables are foreign direct investment (FDI), import, export, gross domestic product (GDP), broad money (M3), and exchange rate (ER). The study adopts panel regression analysis on yearly data covering the period from 2011 to 2020. The pooled OLS regression model, fixed effect regression model (FEM), and random effect regression model (REM) have been employed. With the REM model being suggested as the most suitable model through the Hausman test, the results suggest that FDI, export, GDP, and ER have shown positive and statistically significant influence on both the BSE Shariah and JII. It is also shown that the macroeconomic variables of India and Indonesia are heterogeneities in nature and having mean distribution effects. The study's findings suggest that increasing the possibilities of bilateral trade and investment in the sectors such as health and pharmaceuticals, automotive components, information technology, agro products, and tourism between India and Indonesia will go a long way. It is expediting greater economic activities among these two countries.